Senior High School Students’ Perception of Using Google Classroom at English Teaching and Learning - Nuryati N; Ikariya Sugesti; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2021)
Google Classroom is a new application that used as an online learning media especially in English teaching learning. The objective of this research is to find out the students’ perception on the use of Google Classroom in English teaching learning at eleventh grade of Science Program at MAN 1 Kota Cirebon. Descriptive qualitative was used as the design of this research and the instrument of this research were questionnaire and interview, those were used to describe the students’ perception on the use of Google Classroom as a media in English teaching and learning. The research subject was 28 students eleventh grade of Science Program at MAN 1 Kota Cirebon. Based on the research finding and discussion, it can be concluded that students’ perception in using Google Classroom as an online learning media have positive respond, 92,9 percent of the students were agree that Google Classroom was easy to use and have good performance to used Google Classroom on English teaching and learning process because Google Classroom allow the students to save and retrieve and submit tasks or assignment, information and announcement, attendance list through Google Classroom, and students enthusiastic and interested in English teaching and learning process. In conclusion, Google Classroom is one of the best online learning media in English teaching and learning process especially pandemic period. Keywords: students’ perception; Google Classroom; English teaching learning.